How Halal Labelled Products Influence on Repurchase Intention - Kevin Aushaf Quds; Retno Kusumastuti Hardjono (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2022)
Innovation is a source of competitive advantage. Halal labelled as an output of innovation is still very rare in research and publication. This study examines the influence of innovation attributes on repurchase intention of halal-labelled products of PT Indofood Sukses Makmur Tbk. The respondents are people who have purchased Indofood products and live in Jabodetabek area, amounting to 188 respondents. Data analysis applied simple linear regression test using SPSS software. Quantitative method conducted in this research and data collected through digital form questionnaire derived from each variable. The research results indicated that four dimensions of innovation attributes, namely relative advantage, trialability, observability, and compatibility, have a positive effect on repurchase intention, while one dimension, namely complexity, has a negative effect. It indicates that innovation attributes will be able to increase repurchase intention.  https://doi.org/10.21632/irjbs.15.1.17-25